2015
DOI: 10.1111/phen.12122
|View full text |Cite
|
Sign up to set email alerts
|

Gustatory adaptation affects sexual maturation in male German cockroaches, Blattella germanica

Abstract: Adaptations to hazardous environmental factors are essential for survival, although they may be maladaptive in conditions where the hazard is absent. In German cockroach (Blattella germanica L.) populations, glucose aversion has evolved rapidly in response to glucose-containing insecticidal baits, but little is known about the consequences of this behaviour in the absence of bait. In the present study, glucose-averse (GA) and wild-type (WT) male German cockroaches are restricted to a range of nutritionally def… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 38 publications
0
7
0
2
Order By: Relevance
“…These results add to a growing body of evidence that evolutionary shifts in diet breadth of cockroaches 20,29,30,38,39 may have downstream effects on life history characteristics such as sexual maturation 40 and courtship. 41 We suggest that glucose-averse cockroaches have evolved lower carbohydrate needs, an adaptation that may facilitate the persistence of glucose aversion in German cockroach populations in the absence of selection with glucose-containing baits.…”
Section: Effect Of Protein:carbohydrate Ratio and Sugar Type On Diet mentioning
confidence: 87%
“…These results add to a growing body of evidence that evolutionary shifts in diet breadth of cockroaches 20,29,30,38,39 may have downstream effects on life history characteristics such as sexual maturation 40 and courtship. 41 We suggest that glucose-averse cockroaches have evolved lower carbohydrate needs, an adaptation that may facilitate the persistence of glucose aversion in German cockroach populations in the absence of selection with glucose-containing baits.…”
Section: Effect Of Protein:carbohydrate Ratio and Sugar Type On Diet mentioning
confidence: 87%
“…In addition, we showed that newly eclosed adult GA females matured their oöcytes at a slower rate than WT females on the same laboratory diet, delaying the attainment of sexual receptivity42. Furthermore, in two recent studies we found that GA males had significantly smaller body mass than WT males developing on the same standard laboratory diet4344. Smaller body mass is often a disadvantage in sexual selection due to lower performance under male-male competition and female choice45.…”
mentioning
confidence: 70%
“…In addition, delayed sexual maturation in male GA cockroaches that only had access to glucose-containing food43 may have influenced mating success of these males and given WT males a mating advantage from the start of the experiment. On glucose-free diets, GA and WT males reach sexual maturity at the same age43, and differences in male sexual maturation are therefore not likely to explain the changes in population structure.…”
Section: Discussionmentioning
confidence: 99%
“…Beberapa laporan terkait resistensi perilaku pada kecoak Jerman adalah adanya perilaku glucose aversion/bait version (Silverman & Bieman, 1993), ditemukan 12% starin yang terdeteksi menghindari glukosa dari 41 strain yang diujikan di Malaysia (Lee & Soo, 2002), adanya reaksi menghindari glukosa dan fruktosa serta adaptasi gustatori kecoak Jerman pada populasi kecoak Jerman yang heterogen (Jensen et al, 2016;Jensen et al, 2017;Wang et al, 2004) Di Indonesia juga dilaporkan adanya potensi perkembangan perilaku glucose aversion/bait aversion pada beberapa strain kecoak Jerman (Ambarningrum et al, 2019).…”
Section: Pendahuluanunclassified
“…Berdasarkan uji ketertarikan Kecoak Jerman terhadap fagostimulan berbeda, didapat hasil seperti tertera dalam tabel 1. (Jensen et al, 2016). Adanya sifat omnivora ini didorong dari kebutuhan nutrisi kecoak Jerman akan karbohidrat, lemak, dan protein yang tergolong tinggi, sehingga keempat fagostimulan diatas, dapat dijadikan sebagai bahan umpan (Lauprasert et al, 2006).…”
Section: Hasil Dan Pembahasan Uji Ketertarikan Kecoak Jermanunclassified